Resveratrol's neural protective effects for the injured embryoid body and cerebral organoid - Yanli Wang; Tingting Wei; Qiang Wang; Chaonan Zhang; Keyan Li; Jinbo Deng (BMC, 2022)
Abstract Objective Resveratrol (RSV) is a polyphenol compound found in grapes, veratrum and other plants. It has been reported that RSV has anti-inflammatory, anti-oxidant, anti-cancer and other pharmacological effects. However, the impacts of RSV on development of nervous system are not understood well. The study aims to investigate RSV's neuroprotective effect during development and to provide a health care for pregnant women and their fetuses with RSV supplementation. Methods In this study, we induced human induced pluripotent stem cells (hiPSCs) to form the embryoid bodies (EBs) and cerebral organoids (COs) with 3 dimensional (3D) culture. In the meantime, D-galactose (D-gal, 5 mg/ml) was used to make nervous injury model, and on the other hand, RSV with various doses, such as 2 μm/L, 10 μm/L, 50 μm/L, were applied to understand its neuroprotection. Therefore, the cultures were divided into control group, D-gal nervous injury group and RSV intervention groups. After that, the diameters of EBs and COs were measured regularly under a reverted microscope. In the meantime, the neural proliferation, cell apoptosis and the differentiation of germ layers were detected via immunofluorescence. Results (1) D-gal could delay the development of EBs and COs; (2) RSV could rescue the atrophy of EBs and COs caused by D-gal; (3) RSV showed its neuroprotection, through promoting the neural cell proliferation, inhibiting apoptosis and accelerating the differentiation of germ layers. Conclusion RSV has a neuroprotective effect on the development of the nervous system, suggesting RSV supplementation may be necessary during the health care of pregnancy and childhood.